2017
DOI: 10.1126/science.aam8897
|View full text |Cite
|
Sign up to set email alerts
|

Host DNases prevent vascular occlusion by neutrophil extracellular traps

Abstract: Platelet and fibrin clots occlude blood vessels in hemostasis and thrombosis. Here we report a noncanonical mechanism for vascular occlusion based on neutrophil extracellular traps (NETs), DNA fibers released by neutrophils during inflammation. We investigated which host factors control NETs in vivo and found that two deoxyribonucleases (DNases), DNase1 and DNase1-like 3, degraded NETs in circulation during sterile neutrophilia and septicemia. In the absence of both DNases, intravascular NETs formed clots that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
473
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(498 citation statements)
references
References 29 publications
15
473
0
10
Order By: Relevance
“…A noncanonical pathway to vascular occlusion has recently been demonstrated [54]. It is assumed that NETs have a rather short lifetime in circulation due to the presence of serum DNases.…”
Section: A Link Between Nets Thrombosis and Innate Immunitymentioning
confidence: 99%
“…A noncanonical pathway to vascular occlusion has recently been demonstrated [54]. It is assumed that NETs have a rather short lifetime in circulation due to the presence of serum DNases.…”
Section: A Link Between Nets Thrombosis and Innate Immunitymentioning
confidence: 99%
“…Interestingly, gouty tophi are composed, in part, of aggregated NETs which degrade cytokines and help in the resolution of inflammation (39). Recent studies in mice revealed that a combined deficiency of DNase 1 and DNase1L3 leads to a clotting of vessels by NETs in a disease resembling thrombotic microangiopathies (40). …”
Section: How Cells Die Determines Non-inflammatory Versus Inflammatormentioning
confidence: 99%
“…Of the four members of the DNASE1 family of extracellular DNases, DNASE1 and DNASE1L3 are responsible for nearly all DNase activity in circulation [46,47]. DNASE1 is primarily expressed in the kidneys and gastrointestinal tract, where it helps digest DNA in food.…”
Section: Dna As An Antigen: Origin and Physical Formmentioning
confidence: 99%